ALTERNATIVE SOURCES OF ENTERPRISE FINANCING AND THE IMPACT OF COVID-19 PANDEMIC - Ianioglo, Alina (Economy and Sociology, 2022)
In current conditions of digital transformation and difficulties in accessing traditional financing, alternative sources of finance acquire particular importance. At the same time, the knowledge regarding the alternative finance market in developing countries is yet in its infancy, with little evidence of the effects of the Covid-19 pandemic on the alternative finance market in the Republic of Moldova. Therefore, the article aims to explore financing alternatives for enterprises in the Republic of Moldova and determine the effects of the Covid-19 pandemic on the alternative finance market. Additionally, there were analysed data from other reference countries. In order to achieve the objective of the study, a mixed research approach, based on both primary and secondary data, was used: analysis of statistical data, international rankings, comparison, synthesis, deduction, as well as a questionnaire-based survey designed for small and medium-sized enterprises. SMEs have proven to be vulnerable to crises. The alternative finance market in the Republic of Moldova was analysed, showing that despite a rise in recent years, alternative sources of financing are still poorly developed. The study shows that enterprises face the biggest problems in accessing venture capital, financing on the securities market and use of electronic platforms to attract funding (crowdfunding, cryptocurrencies, etc.). At the same time, there was registered an improvement in accessing crowdfunding since the beginning of the pandemic. Generally, obtained results are essential for further research, practitioners and in determining measures to facilitate access to finance.